Cluster Computing The Journal of Networks, Software Tools and Applications - Hariri, Salim; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Cluster Computing: the Journal of Networks, Software Tools and Applications will provide a forum for presenting the latest research and technology that unify the fields of parallel processing, distributed computing systems and high performance computer networks. The current advances in computing, networking technology and software have spurred a lot of research interest in cluster and internet computing, as demonstrated in Cloud and Grid computing, and distributed high performance data centers. In the last few years, we have seen an increased interest in developing applications, software tools, communications protocols and high performance data centers, Grids and cloud computing sites to capitalize on these advances and initiatives. Publications about these developments currently appear in several journals that either focus on the communications field, or on parallel and distributed computing with a strong emphasis on the parallel algorithms. Cluster Computing Journal will uniquely address the latest results in integrating these three fields to support the development of high performance parallel distributed computing systems and their applications. The journal will be an important source of information for the growing number of researchers, developers and users of High Performance Parallel and Distributed Computing environments. In these environments, parallel and/or distributed computing techniques are applied to the solution of large-scale scientific and engineering applications running on clusters, cloud computing and/or distributed data centers. Presents the latest research and applications in parallel and distributed algorithms, high performance distributed computing systems that include Clouds, Grids, and Data Centers Discusses distributed computing techniques as applied to the solution of large-scale scientific and engineering applications running on high performance parallel and distributed computing systems An important source of information for the growing number of researchers, developers and users of parallel and distributed computing systems.
Keywords: Microprocessors; Computer communication systems; Operating systems (Computers).; Processor Architectures; Operating Systems; Computer Communication Networks